2018
DOI: 10.1108/ijm-03-2017-0053
|View full text |Cite
|
Sign up to set email alerts
|

The contrary effects of intrinsic and extrinsic motivations on burnout and turnover intention in the public sector

Abstract: Purpose Based on motivation theories, such as self-determination theory, the purpose of this paper is to examine whether intrinsic and extrinsic motivations significantly influence burnout and turnover intention in the public sector. Furthermore, the authors assessed the mediating effect of organizational citizenship behavior (OCB) and public service motivation (PSM) on the relationship between intrinsic/extrinsic motivation and burnout/turnover intention. Design/methodology/approach Based on a survey of 203… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 39 publications
4
52
1
2
Order By: Relevance
“…Results have shown significant influence of organizational environment on employee retention and supported by Khuong andLe Vu (2014) Danish et al (2013); Hanaysha (2016). Similarly, significant relationship between intrinsic motivation and employee retention was found and in line with Deci and Ryan (1985); Deci & Ryan, (2000); Kim (2018);Martín Cruz et al (2009). Transformational leadership had significant influence on employee retention and supported by Bass (1985); Nielsen et al (2008); Para-González et al (2018); Rafferty and Griffin (2004); Yizhong et al (2019).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Results have shown significant influence of organizational environment on employee retention and supported by Khuong andLe Vu (2014) Danish et al (2013); Hanaysha (2016). Similarly, significant relationship between intrinsic motivation and employee retention was found and in line with Deci and Ryan (1985); Deci & Ryan, (2000); Kim (2018);Martín Cruz et al (2009). Transformational leadership had significant influence on employee retention and supported by Bass (1985); Nielsen et al (2008); Para-González et al (2018); Rafferty and Griffin (2004); Yizhong et al (2019).…”
Section: Discussionmentioning
confidence: 59%
“…Another research conducted by Martín Cruz et al (2009) showed that intrinsic motivation significantly influences on employee motivation to perform a job accurately. Intrinsic motivation in workplace is studied by several researchers (Deci & Ryan, 1985, 2000Kim, 2018;Martín Cruz et al, 2009). Intrinsic motivation significantly influences on employee retention and enhances organizational performance (Martín Cruz et al, 2009).…”
Section: Intrinsic Motivation (Imot)mentioning
confidence: 99%
See 1 more Smart Citation
“…The mean value of OCB in this research suggests that future studies may examine other associated outcomes such as intention to leave (Kim 2018) or job embeddedness theory that have been found in previous empirical studies (see Lee, Burch, and Mitchell 2014). Additionally, future studies may consider the examination on specific types of leadership behaviours such as paternalistic leadership prevalent in a similar context like Vietnam in the relationships of respect, public service motivation, and work behaviours.…”
Section: Limitations and Future Researchmentioning
confidence: 63%
“…Also, intrinsic motivation occasions less averseness of work, piloting employees to work relentlessly, intelligently, lengthily, and more creatively (Gagné et al, 2015). Intrinsic motivation has been seen as a precursor to higher performance on the job (Rich, Lepine, Crawford, 2010), organisational citizenship behaviour (Lazauskaite-Zabielske, Urbanaviciute, Bagdziuniene, 2015), and turnover intentions (Kim, 2018). But it is rarely researched as a corollary of some prosocial practices in the workplace.…”
Section: Introductionmentioning
confidence: 99%